The Effect Of Leaflet-Based Health Education On Breastfeeding On Increasing Knowledge - Dewi Parwati; Norma Safitri; Musdalifah Musdalifah (International Forum of Researchers and Lecturers, 2025)
Breast Self-Examination (BSE) is an important action in the early detection of breast cancer. Early detection plays a crucial role in increasing the success rate of treatment and reducing mortality from breast cancer. This study aims to determine the effect of leaflet-based health education about BSE on increasing knowledge among Women of Childbearing Age in the Tarailu Health Center Work Area, Mamuju Regency. The research method used is quantitative research with a Quasi-Experimental research design and a